Healthy home interventions: Distribution of PM2.5 emitted during cooking in residential settings. (January 2022) - Liu, Qingyang; Son, Young Joo; Li, Linhao; Wood, Nadia; Senerat, Araliya M.; Pantelic, Jovan
Abstract: The current study investigated the emission, distribution, and removal of cooking-emitted particles in the simulated residential module of the Well Living Lab. Cooking experiments were conducted following a standardized protocol under different interventions. Cooking experiments consisted of frying bacon that emitted 2.35 × 10 3 (2.22 × 10 3 ) μg/min of PM2.5 . Interventions studied included: Ventilation; a combination of Ventilation and Stove Hood; combination of Ventilation and Portable Air Cleaners; Air Flush; and combination of Air Flush, Stove Hood, and Bathroom Exhaust. The impact of door configuration was also assessed. Particulate Matter (PM2.5 ) and CO2 sensors were distributed in all spaces. A method based on CO2 traced decay was used to characterize airflow. Particle removal rate and integrated PM2.5 concentration were used to compare the capability of different interventions in removing PM2.5 and reducing particle exposure. The combination of Ventilation and Stove Hood and the combination of Air Flush, Stove Hood, and Bathroom Exhaust showed the best performance in reducing the integrated PM2.5 concentration of cooking-emitted particles. Particle Removal Rate showed that cooking-emitted PM2.5 were most effectively removed by the combination of Ventilation and Portable Air Cleaners. Air Flush was not a very effective method in removing cooking-emitted particles even with the 2.5 times increase of the supply flow rate (4 h −1 in the residential module). Closing bedroom and/or bathroom doors changed particle distribution and increased PM2.5 concentration in the kitchen and living room. Highlights: Adding a stove hood performed the best in reducing PM2.5 concentration. Ventilation and PACs combined was most effective in removing cooking-emitted PM2.5. Air Flush was not effective in removing cooking-emitted particles. Frying bacon emits 2.35 × 10 3 (2.22 × 10 3 ) μg/min of PM2.5 .